Identifying Male California Scale Insects - N. D., Makhmudova (American Journal of Biology and Natural Sciences, 2024)
The presence of dangerous coccids is a pervasive phenomenon in Uzbekistan. Of these, the Californian shield bug is classified as a quarantine pest. It causes extensive damage to a wide variety of plants. It causes damage to a wide range of crops, including apple, pear, plum, quince, peach, almonds, hawthorn, elm, poplar, and others. The first-instar diapausing larvae overwinter with a dark grey or black shield. In spring, the insect feeds intensively and molts, forming a shield similar to that of an adult female. Following the second molt, adult females are formed. After mating, the female spawns larvae of strollers, which spread along branches and leaves and can also settle on fruits, thereby initiating the next generation. This article will examine the means of distinguishing between the male and female California shield insects.